Influencia de las características físicas y químicas del suelo sobre la estructura y composición florística en diferentes fisonomías en el sector caballococha -palo seco- buen suceso, loreto - Perú - Burga Alvarado, Ronald (2008)
Tropical rain forests are ecosystems housing a great number and variety of species. Floristic composition, structure and physical and chemical characteristics of soils of Caballococha-Palo Seco-Buen Suceso sector was analyzed. Data were collected by means of a stratified forest inventory at the reconnaissance level using sample units of 1 ha, tree DBH ≥ 27,5cm, commercial height, total height and common name of species were also recorded. The 15 families with the highest number of genera and species account for the 69,08% and 71,71% of total of species. The moderately dissected high-humid terrace forest features the highest number of species (n=135), density (d= 162,25 trees/ha), basal cover (Ba= 27,38 m2/ha) and volume (V= 315,71 m3/ha), whereas the lowest number of species (n=30), density (d= 69,00 trees/ha), basal cover (Ba= 10,98 m2/ha) and volume (v = 135,14 m3/ha) occurs in the low-humid terrace forest. The highest IVI (272,58%) is found in the low-humid terrace forest and the lowest IVI (168,66%) occurs in the moderately dissected highhumid terrace forest. The distribution of basal area indicates an immature forest recovering from man disturbance. In general terms tropical rain forests of the study site shows a low natural fertility.